2014
DOI: 10.1094/mpmi-08-13-0231-r
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Sequence Motifs Essential for P0-Mediated Suppression of RNA Silencing in an Isolate of Potato leafroll virus from Inner Mongolia

Abstract: Polerovirus P0 suppressors of host gene silencing contain a consensus F-box-like motif with Leu/Pro (L/P) requirements for suppressor activity. The Inner Mongolian Potato leafroll virus (PLRV) P0 protein (P0(PL-IM)) has an unusual F-box-like motif that contains a Trp/Gly (W/G) sequence and an additional GW/WG-like motif (G139/W140/G141) that is lacking in other P0 proteins. We used Agrobacterium infiltration-mediated RNA silencing assays to establish that P0(PL-IM) has a strong suppressor activity. Mutagenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
93
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(102 citation statements)
references
References 60 publications
8
93
1
Order By: Relevance
“…By mutagenizing the LP residues of either of the two motifs, the authors demonstrated that only the second motif was essential to block RNA silencing. Despite this, and unlike our observations, Zhuo et al (2014) were unable to show any interaction between P0 PL-IM and NbSKP1 (N. benthamiana ortholog of ASK1), suggesting that ubiquitination by a P0 PL-IM -containing SCF-type E3 ligase was not required for AGO1 degradation. A second imperfect F-boxlike motif was found in both P0 RPV and P0 RPS at the same position as the downstream F-box motif of P0 PL-IM (Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…By mutagenizing the LP residues of either of the two motifs, the authors demonstrated that only the second motif was essential to block RNA silencing. Despite this, and unlike our observations, Zhuo et al (2014) were unable to show any interaction between P0 PL-IM and NbSKP1 (N. benthamiana ortholog of ASK1), suggesting that ubiquitination by a P0 PL-IM -containing SCF-type E3 ligase was not required for AGO1 degradation. A second imperfect F-boxlike motif was found in both P0 RPV and P0 RPS at the same position as the downstream F-box motif of P0 PL-IM (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…Intriguingly, although P0 PL-IM shares poor amino acid conservation with P0 RPV and P0 RPS , the sequence alignment highlights the first WG motif in common (Fig. 6) that was determined to play an essential role in suppression of RNA silencing of the P0 PL-IM (Zhuo et al, 2014). This could point to another functional domain in CYDV P0s that may participate in a suppressor-related function, for instance in AGO1 binding.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations